On the challenges and opportunities facing fish biology: a discussion of five key knowledge gaps. Issue 3 (14th March 2018) - Jacobs, A.; Doran, C.; Murray, D. S.; Duffill Telsnig, J.; Laskowski, K. L.; Jones, N. A. R.; Auer, S. K.; Præbel, K.
Abstract : Many fish species face increasing challenges associated with climate change and overfishing. At the same time, aquaculture is becoming vital for food security. Gaining a deeper understanding of the basic biology of fish is therefore more important than ever. Here we synthesize and summarize key questions, opportunities and challenges in fish biology highlighted during a round‐table discussion at the 50th Anniversary Symposium of The Fisheries Society of the British Isles, held at the University of Exeter, U.K., in July 2017. We identified several knowledge gaps but also key opportunities for fish biology to inform food security, for collective behaviour, evolutionary history and trait correlations to predict responses to environmental change and for novel analytical approaches to mine existing data sets. Overall, more integrative approaches through stronger collaborations across different fields are needed to advance our understanding of the basic biology of fish.